(untitled) - Loberger, Gordon J. (New York, NY, 2001)
This handbook covers all the basics of standard English usage in a concise, step-by-step format including the special "General Observation" feature that provides grammar rules and tips at a glance. This comprehensive reference is the perfect desktop reference for the non-writing professionals and students alike
Keywords: English language; Grammar